2023
DOI: 10.1007/s00018-023-04859-9
|View full text |Cite|
|
Sign up to set email alerts
|

Autophagy protein 5 controls flow-dependent endothelial functions

Abstract: Dysregulated autophagy is associated with cardiovascular and metabolic diseases, where impaired flow-mediated endothelial cell responses promote cardiovascular risk. The mechanism by which the autophagy machinery regulates endothelial functions is complex. We applied multi-omics approaches and in vitro and in vivo functional assays to decipher the diverse roles of autophagy in endothelial cells. We demonstrate that autophagy regulates VEGF-dependent VEGFR signaling and VEGFR-mediated and flow-mediated eNOS act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 78 publications
0
1
0
Order By: Relevance
“…This indicates that, at the time of diagnosis, AML cells with higher basal autophagic activity are associated with low ERE levels, and vice versa. Additionally, we downloaded data from previously published studies performing autophagy inhibitions [ 51 , 52 ] and observed that autophagy inhibition, whether genetic or chemical, resulted systematically in the upregulation of EREs (Fig. 5F ).…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that, at the time of diagnosis, AML cells with higher basal autophagic activity are associated with low ERE levels, and vice versa. Additionally, we downloaded data from previously published studies performing autophagy inhibitions [ 51 , 52 ] and observed that autophagy inhibition, whether genetic or chemical, resulted systematically in the upregulation of EREs (Fig. 5F ).…”
Section: Resultsmentioning
confidence: 99%
“…The inhibition of autophagy in these cells impaired VEGF-induced angiogenesis [80,81]. In mice, ATG5 deficiency also leads to impaired VEGF-and flow-mediated neoangiogenesis in both microvascular and macrovascular beds [82]. Further work is needed to elucidate autophagy's exact function in vessel development.…”
Section: Autophagy-mediated Regulation Of Angiogenesismentioning
confidence: 99%